Women in Biotechnology Creating Interfaces - Molfino, Francesca; Zucco, Flavia (Springer Netherlands : Imprint: Springer, 2008)
Women in Biotechnology presents a unique study of the relationships and communications between women scientists, particularly those working in biotechnology. This is achieved by creating interfaces or collecting different points of view over several disciplines (i.e. economy, sociology, biology, genetics) to bridge the communication gap among science, the humanities and different feminist groups. The publication of this book is the first step in building a new scientific community that shares a common interest in improving the awareness of women scientists who are not an integral part of the decision-making processes in their respective fields. In this respect, Women in Biotechnology endeavours to address the ethical and bio-political implications in the different branches of contemporary research, and to promote the need of women holding decision-making power to consolidate the scientific and social responsibility to all scientists.